2016
DOI: 10.1155/2016/4095723
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Brain-Derived Neurotrophic Factor as a Biomarker for the Main Types of Mild Neurocognitive Disorders and Treatment Efficacy: A Preliminary Study

Abstract: Decreased levels of brain-derived neurotrophic factor (BDNF) are assumed to play a crucial role in the pathophysiology of mild neurocognitive disorders (MNCDs). In this study, we compared plasma BDNF levels (at baseline and after two months of treatment with escitalopram) in patients with the main types of MNCDs and normal controls. 21 patients met the DSM-5 diagnostic criteria for possible MNCD due to Alzheimer's disease (MNCD-AD); 22 patients fulfilled the diagnostic criteria for subcortical vascular MNCD (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…A positive correlation between BDNF level and the MMSE scale was previously shown by Belviranli et al (2016) who investigated the dependence of cognitive parameters (assessed by MMSE) and BDNF plasma level in endurance athletes. Similarity, Levada et al (2016) observed that after BDNF administration in patients with mild neurocognitive disorders, their MMSE level increased. The decline in parameters on the GDS scale was about 50% greater in the ELF-EMF group, in comparison to the non-ELF-EMF group.…”
Section: Discussionsupporting
confidence: 58%
“…A positive correlation between BDNF level and the MMSE scale was previously shown by Belviranli et al (2016) who investigated the dependence of cognitive parameters (assessed by MMSE) and BDNF plasma level in endurance athletes. Similarity, Levada et al (2016) observed that after BDNF administration in patients with mild neurocognitive disorders, their MMSE level increased. The decline in parameters on the GDS scale was about 50% greater in the ELF-EMF group, in comparison to the non-ELF-EMF group.…”
Section: Discussionsupporting
confidence: 58%
“…Reductions in BDNF are often associated with mood disorders (reviewed in Hashimoto, 2010; Moonat et al, 2011) and cognitive impairments (Levada et al, 2016); however, elevations in BDNF are also reported in bipolar disorder (Barbosa et al, 2013) as well as in inflammatory conditions with a high prevalence of co-morbid depression and anxiety such as fibromyalgia (Epstein et al, 1999; Haas et al, 2010; Okifuji et al, 2000). Thus, alcohol-related neuropsychiatric symptoms may share common pathways with neuropsychiatric symptoms observed in fibromyalgia and in mental health disorders potentially mediated via inflammatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF mRNA and protein levels are also reduced in cognition-related structures such as hippocampus and frontal cortex, which corroborates BDNF depletion to be involved in the cognitive deficit leading to AD dementia [ 139 ]. BDNF levels are also reduced in plasma of patients with mild cognitive impairment (MCI) [ 140 ] and AD [ 141 ]. AD patients with higher serum concentrations of BDNF showed less cognitive decline after 1 year; this effect was more pronounced in the more severe stages of the disease [ 142 , 143 ].…”
Section: Bdnf In Neurodegenerative Disordersmentioning
confidence: 99%